Alterations in Abundance and Compartmentalization of miRNAs in Blood Plasma Extracellular Vesicles and Extracellular Condensates during HIV/SIV Infection and Its Modulation by Antiretroviral Therapy (ART) and Delta-9-Tetrahydrocannabinol (Δ9-THC) - Steven Kopcho; Marina McDew-White; Wasifa Naushad; Mahesh Mohan; Chioma M. Okeoma (Viruses, 2023)
In this follow-up study, we investigated the abundance and compartmentalization of blood plasma extracellular miRNA (exmiRNA) into lipid-based carriers—blood plasma extracellular vesicles (EVs) and non-lipid-based carriers—extracellular condensates (ECs) during SIV infection. We also assessed how combination antiretroviral therapy (cART), administered in conjunction with phytocannabinoid delta-9-tetrahydrocannabinol (THC), altered the abundance and compartmentalization of exmiRNAs in the EVs and ECs of SIV-infected rhesus macaques (RMs). Unlike cellular miRNAs, exmiRNAs in blood plasma may serve as minimally invasive disease indicators because they are readily detected in stable forms. The stability of exmiRNAs in cell culture fluids and body fluids (urine, saliva, tears, cerebrospinal fluid (CSF), semen, blood) is based on their association with different carriers (lipoproteins, EVs, and ECs) that protect them from the activities of endogenous RNases. Here, we showed that in the blood plasma of uninfected control RMs, significantly less exmiRNAs were associated with EVs compared to the level (30% higher) associated with ECs, and that SIV infection altered the profile of EVs and ECs miRNAome (Manuscript 1). In people living with HIV (PLWH), host-encoded miRNAs regulate both host and viral gene expression, which may serve as indicators of disease or treatment biomarkers. The profile of miRNAs in blood plasma of PLWH (elite controllers versus viremic patients) are different, indicating that HIV may alter host miRNAome. However, there are no studies assessing the effect of cART or other substances used by PLWH, such as THC, on the abundance of exmiRNA and their association with EVs and ECs. Moreover, longitudinal exmiRNA profiles following SIV infection, treatment with THC, cART, or THC+cART remains unclear. Here, we serially analyzed miRNAs associated with blood plasma derived EVs and ECs. Methods: Paired EVs and ECs were separated from EDTA blood plasma of male Indian rhesus macaques (RMs) in five treatment groups, including VEH/SIV, VEH/SIV/cART, THC/SIV, THC/SIV/cART, or THC alone. Separation of EVs and ECs was achieved with the unparalleled nano-particle purification tool ─PPLC, a state-of-the-art, innovative technology equipped with gradient agarose bead sizes and a fast fraction collector that allows high resolution separation and retrieval of preparative quantities of sub-populations of extracellular structures. Global miRNA profiles of the paired EVs and ECs were determined with RealSeq Biosciences (Santa Cruz, CA) custom sequencing platform by conducting small RNA (sRNA)-seq. The sRNA-seq data were analyzed using various bioinformatic tools. Validation of key exmiRNA was performed using specific TaqMan microRNA stem-loop RT-qPCR assays. Results: We investigated the effect of cART, THC, or both cART and THC together on the abundance and compartmentalization of blood plasma exmiRNA in EVs and ECs in SIV-infected RMs. As shown in Manuscript 1 of this series, were in uninfected RMs, ~30% of exmiRNAs were associated with ECs, we confirmed in this follow up manuscript that exmiRNAs were present in both lipid-based carriers—EVs and non-lipid-based carriers—ECs, with 29.5 to 35.6% and 64.2 to 70.5 % being associated with EVs and ECs, respectively. Remarkably, the different treatments (cART, THC) have distinct effects on the enrichment and compartmentalization pattern of exmiRNAs. In the VEH/SIV/cART group, 12 EV-associated and 15 EC-associated miRNAs were significantly downregulated. EV-associated miR-206, a muscle-specific miRNA that is present in blood, was higher in the VEH/SIV/ART compared to the VEH/SIV group. ExmiR-139-5p that was implicated in endocrine resistance, focal adhesion, lipid and atherosclerosis, apoptosis, and breast cancer by miRNA-target enrichment analysis was significantly lower in VEH/SIV/cART compared to VEH/SIV, irrespective of the compartment. With respect to THC treatment, 5 EV-associated and 21 EC-associated miRNAs were significantly lower in the VEH/THC/SIV. EV-associated miR-99a-5p was higher in VEH/THC/SIV compared to VEH/SIV, while miR-335-5p counts were significantly lower in both EVs and ECs of THC/SIV compared to VEH/SIV. EVs from SIV/cART/THC combined treatment group have significant increases in the count of eight (miR-186-5p, miR-382-5p, miR-139-5p and miR-652, miR-10a-5p, miR-657, miR-140-5p, miR-29c-3p) miRNAs, all of which were lower in VEH/SIV/cART group. Analysis of miRNA-target enrichment showed that this set of eight miRNAs were implicated in endocrine resistance, focal adhesions, lipid and atherosclerosis, apoptosis, and breast cancer as well as cocaine and amphetamine addiction. In ECs and EVs, combined THC and cART treatment significantly increased miR-139-5p counts compared to VEH/SIV group. Significant alterations in these host miRNAs in both EVs and ECs in the untreated and treated (cART, THC, or both) RMs indicate the persistence of host responses to infection or treatments, and this is despite cART suppression of viral load and THC suppression of inflammation. To gain further insight into the pattern of miRNA alterations in EVs and ECs and to assess potential cause-and-effect relationships, we performed longitudinal miRNA profile analysis, measured in terms of months (1 and 5) post-infection (MPI). We uncovered miRNA signatures associated with THC or cART treatment of SIV-infected macaques in both EVs and ECs. While the number of miRNAs was significantly higher in ECs relative to EVs for all groups (VEH/SIV, SIV/cART, THC/SIV, THC/SIV/cART, and THC) longitudinally from 1 MPI to 5 MPI, treatment with cART and THC have longitudinal effects on the abundance and compartmentalization pattern of exmiRNAs in the two carriers. As shown in Manuscript 1 where SIV infection led to longitudinal suppression of EV-associated miRNA-128-3p, administration of cART to SIV-infected RMs did not increase miR-128-3p but resulted in longitudinal increases in six EV-associated miRNAs (miR-484, miR-107, miR-206, miR-184, miR-1260b, miR-6132). Furthermore, administration of cART to THC treated SIV-infected RMs resulted in a longitudinal decrease in three EV-associated miRNAs (miR-342-3p, miR-100-5p, miR181b-5p) and a longitudinal increase in three EC-associated miRNAs (miR-676-3p, miR-574-3p, miR-505-5p). The longitudinally altered miRNAs in SIV-infected RMs may indicate disease progression, while in the cART Group and the THC Group, the longitudinally altered miRNAs may serve as biomarkers of response to treatment. Conclusions: This paired EVs and ECs miRNAome analyses provided a comprehensive cross-sectional and longitudinal summary of the host exmiRNA responses to SIV infection and the impact of THC, cART, or THC and cART together on the miRNAome during SIV infection. Overall, our data point to previously unrecognized alterations in the exmiRNA profile in blood plasma following SIV infection. Our data also indicate that cART and THC treatment independently and in combination may alter both the abundance and the compartmentalization of several exmiRNA related to various disease and biological processes.